Optimasi Formula Krim Ekstrak Daun Katuk (Sauropus Androgynus) Variasi Konsentrasi Asam Stearat, Trietanolamin, dan Gliserin - Lestari, Febia Arien; Hajrin, Wahida; Hanifa, Nisa Isneni (Jurnal Kefarmasian Indonesia, 2020)
Sauropus androgynus (L.) Merr.) contain secondary metabolite compounds: flavonoids and polyphenols which has bioactivity as antioxidants. Antioxidants act as photoprotector, so it can be formulated into sun protection product. The selection of cream base is very important due to it’s not only as vehicle of active ingredients but also affecting cream’s physical properties and effectiveness. This study aims to determine the composition of the optimum base formula and evaluation formula cream of extract katuk leaves with variations concentration of stearic acid, TEA, and glycerin. Formula optimization was conducted through the Simplex Lattice Design methode with 13 formulas. The results of evaluation were processed with Design Expert software. The optimum formula was respectively at 13.16% stearic acid, 12% glycerin, and 3.84% TEA. The optimum formula cream evaluation was spreadability in 4.89 cm, 0.56 s stickiness power, and pH 6,1. Acceptability test results showed that the cream could accepted by society very well.